AN ANALYSIS OF READING MATERIALS IN “BAHASA INGGRIS” TEXTBOOK FOR VOCATIONAL HIGH SCHOOL STUDENTS - Radiatul Aslamiyah; Akhmad Ali Mirza; Hesty Widiastuty (IKIP Siliwangi, 2022)
The purpose of this research is to describe the relevance of reading materials in the “Bahasa Inggris” textbook for Vocational High School students in the XI grade, as well as the good textbook criteria proposed by Pusat Perbukuan, the Ministry of National Education, in terms of content, presentation, language use, and readability. The research used a descriptive qualitative study with a content analysis design. The instruments used to collect the data were a document study and observation in the form of checklists. The results demonstrated that the textbook